Antiproliferative Activity of Gold(III) Complexes with Esters of Cyclohexyl-Functionalized Ethylenediamine-N,N’-Diacetate - Pantelić Nebojša (Serbian Journal of Experimental and Clinical Research, 2017)
Six gold(III) complexes with esters of cyclohexyl-functionalized ethylenediamine-N,N’-diacetate, general formula [AuCl2{(S,S)-R2eddch}]PF6, [(S,S)-eddch = (S,S)-ethylenediamine-N,N’-di-2-(3-cyclohexyl)propanoate, R = Me, Et, n-Pr, n-Bu, i-Bu, i-Am, 1–6, respectively], were tested against cancer cell lines such as human melanoma Fem-x, human colon carcinoma LS174T and non-small cell lung carcinoma A549 as well as a non-cancerous human embryonic lung fibroblasts MRC-5 using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay with the aim of assessing in vitro antitumoral activity and selectivity. All investigated complexes showed lower cytotoxicity and better or similar selectivity in comparison to cisplatin, used as reference compound. Complex [AuCl2{(S,S)-(i-Am)2eddch}]PF6 (6) demonstrated the highest activity against Fem-x (IC50 = 14.98 ± 0.34 μM). Additionally, the same complex expressed 4.5 times higher selectivity than cisplatin.